TMC function, dysfunction, and restoration in mouse vestibular organs - Ratzan, Evan M.; Lee, John; Madison, Margot A.; Zhu, Hong; Zhou, Wu; Géléoc, Gwenaëlle S. G.; Holt, Jeffrey R. (Frontiers in Neurology, 2024)
Tmc1 and Tmc2 are essential pore-forming subunits of mechanosensory transduction channels localized to the tips of stereovilli in auditory and vestibular hair cells of the inner ear. In vestibular organs, Tmc1 and Tmc2 show dynamic developmental changes, differences in regional expression patterns, and overall expression levels, which differ between the utricle and saccule. These underlying changes contribute to unanticipated phenotypic loss of vestibular signaling in Tmc1 KO mice, measured as vestibular sensory evoked potentials (VsEPs) and vestibulo-ocular reflexes (VORs). In contrast, Tmc2 KO mice retain VsEPs despite the loss of the calcium buffering protein calretinin, a characteristic biomarker of mature striolar calyx-only afferents. We find neonatal Tmc1 gene replacement therapy is sufficient to restore linear VsEP in Tmc1 KO mice for up to six months post-injection.